Evidence of Convergent and Discriminant Validity of TAI-State: Influence of Pre-exam Coping Strategies - Dominguez-Lara, Sergio Alexis (2018)
The objective was to find out the degree to which the pre-exam coping strategies (PECS) influence the Test Anxiety (TA) – State (TA-State) in psychology students in order to obtain convergent and discriminating evidence from the TAI-State. The study included 156 psychology students (115 women) from a private university in Metropolitan Lima, ages ranging from 18 to 42 (M = 22.51). The instruments used were: Test Anxiety Inventory-State (TAI-State) and the Coping with Pre-Exam Anxiety and Uncertainty-Brief (COPEAU-B), which evaluates four strategies. A confirmatory factor analysis was used to verify reliability and validity; while structural equation models were used to assess the research model. After the structural regression analysis, the PECSs explain 13.3% of the variance of the TA-State, with task-oriented and search for social support for instrumental reasons strategies as the most influential (β = -.212 and β = .320). The theoretical and practical implications of the study are discussed.